2016
DOI: 10.3390/e18070246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Percutaneous Coronary Intervention Procedure on Heart Rate Variability and Pulse Transit Time Variability: A Comparison Study Based on Fuzzy Measure Entropy

Abstract: Percutaneous coronary intervention (PCI) is a common treatment method for patients with coronary artery disease (CAD), but its effect on synchronously measured heart rate variability (HRV) and pulse transit time variability (PTTV) have not been well established. This study aimed to verify whether PCI for CAD patients affects both HRV and PTTV parameters. Sixteen CAD patients were enrolled. Two five-minute ECG and finger photoplethysmography (PPG) signals were recorded, one within 24 h before PCI and another wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The possible reason can be explained that with the decrease of left ventricular function, the activity of peripheral sympathetic nerve is stimulated, and the tension of the artery is enhanced while its elasticity is decreased, resulting in a shorter PTT. The proof can be also from other studies in [40] and [41], where significant increase in PTT was observed within 24 h after percutaneous coronary intervention (PCI) procedure for coronary artery disease patients, indicating that PCI procedure is helpful for improving arterial elasticity and left ventricular functions.…”
Section: Discussionsupporting
confidence: 57%
“…The possible reason can be explained that with the decrease of left ventricular function, the activity of peripheral sympathetic nerve is stimulated, and the tension of the artery is enhanced while its elasticity is decreased, resulting in a shorter PTT. The proof can be also from other studies in [40] and [41], where significant increase in PTT was observed within 24 h after percutaneous coronary intervention (PCI) procedure for coronary artery disease patients, indicating that PCI procedure is helpful for improving arterial elasticity and left ventricular functions.…”
Section: Discussionsupporting
confidence: 57%
“…Although the pulse signal is different from the electric one generated by the heart activity, due to their own natures, the two are strongly related. Obviously, due to a mechanical delay of approximately 200 ms [3], they are not synchronized, but, on the other hand, they show the same trend since the pressure wave frequency corresponds to the heart beating. Therefore, analyzing the pulse signal is possible to retrieve the heart rate (HR).…”
Section: Introductionmentioning
confidence: 99%